Policy making for vaccine use as a driver of vaccine innovation and development in the developed world. Issue 10 (7th March 2017) - Seib, Katherine; Pollard, Andrew J.; de Wals, Philippe; Andrews, Ross M.; Zhou, Fangjun; Hatchett, Richard J.; Pickering, Larry K.; Orenstein, Walter A.
Highlights: Epidemiology and vaccine safety/efficacy have driven vaccine policy, a pull mechanism for development. New complex technologies are expected to dominate future vaccine development. Attributes like duration of immunity, vaccine safety and program implementation feasibility may drive future recommendations. Vaccine innovation faces economic hurdles as vaccine development becomes more complex. Risk-mitigating strategies will be important to spur major advances in vaccine technologies. Abstract: In the past 200 years, vaccines have had unmistakable impacts on public health including declines in morbidity and mortality, most markedly in economically-developed countries. Highly engineered vaccines including vaccines for conditions other than infectious diseases are expected to dominate future vaccine development. We examine immunization vaccine policy as a driver of vaccine innovation and development. The pathways to recommendation for use of licensed vaccines in the US, UK, Canada and Australia have been similar, including: expert review of disease epidemiology, disease burden and severity; vaccine immunogenicity, efficacy and safety; programmatic feasibility; public demand; and increasingly cost-effectiveness. Other attributes particularly important in development of future vaccines are likely to include: duration of immunity for improved vaccines such as pertussis; a greater emphasis on optimizing community protection rather than direct protection only; programmatic implementation, feasibility, improvements (as in the case of development of a universal influenza vaccine); public concerns/confidence/fears related to outbreak pathogens like Ebola and Zika virus; and major societal burden for combating hard to treat diseases like HIV and antimicrobial resistant pathogens. Driving innovation and production of future vaccines faces enormous economic hurdles as available approaches, technologies and regulatory pathways become more complex. As such, cost-mitigating strategies and focused, aligned efforts (by governments, private organizations, and private-public partnerships) will likely be needed to continue to spur major advances in vaccine technologies and development.